Improvement of the Upper Extremity at the Subacute Stage Poststroke: Does Hand Dominance Play a Role?. (November 2020) - Hmaied Assadi, Samar; Feige Gross-Nevo, Revital; Dudkiewicz, Israel; Barel, Haim; Rand, Debbie
Background: The impact of hand dominance on the expected (motor and functional ability and daily use) improvement of the affected upper extremity (UE) in subacute stroke has not yet been investigated. Objectives: To compare between the affected dominant and affected nondominant UE (1) on rehabilitation admission (T1) for motor and sensory abilities, functional ability, and daily use and (2) 6 weeks poststroke onset (T2) and the UE recovery between T1 and T2 regarding percent change, improvement effect size, and percent of participants achieving minimal clinical important difference (MCID). Methods: Multicenter longitudinal study. Results: Thirty-eight participants with affected dominant and 51 participants with affected nondominant UE were recruited. On T1 and T2, between-group differences were not seen for all UE variables. Significant improvement in the motor and functional ability, daily use, and perceived recovery between T1 and T2 were seen for the affected dominant ( z = −3.01 to −4.13, P < .01) and nondominant UEs ( z = −4.59 to −5.32, P < .01). Effect size improvement values were moderate and large in the affected dominant and nondominant UE (respectively). In addition, 14% to 40% of the participants in both UEs achieved MCID. Conclusions: Significant and similar clinical meaningfulness in UE improvement can be expected during subacute rehabilitation; however, improvement magnitude and percent improvement is different for the UE domains of the affected dominant and the affected nondominant UEs. These findings highlight the distinct roles of the dominant and nondominant hands during bimanual daily activities, which can guide clinicians during stroke rehabilitation.